TOPLUMSAL BiR ZORUNLULUK : BiR ARADA YAŞAMAK - Güneş, Abdurrahman (Fırat University, 2005)
A.Muslim learned Ibn Haldun says that it is compulsory for human being to live together. A religion's universality and it' s being used is evaluated how it regards the other religions and belief. When prophet Muhammed went to Medine he Prepared the first Constitution of Islam in the history of Islam in 622 (The Medine City-state Constitution). This constitution was prepared for the ditferent cuitures and religions so that they could live together. Islam is the religion of the tolerance. All the different religions' and cultural elements' rights have been protected in Islamic law. There is no using force in Islam. Islam has announcement and invitation. Announcement and invitation are not used by force but by giving information. In the Koran prophet Muhammed is asked to give advice."You are the one who gives advice, you are not the one who is a force upon people" the Koran says.
Keywords: Religious Studies; Din Araştırmaları